Performance evaluation of the developed combined lines seeder through the forward speeds and seeding rates - Ali J. Shannon1‎ (University of Thi-Qar Journal of agricultural research, 2024)
The field experiment was conducted in one of the fields of Maysan Governorate / Al-Batira region in a silty clay soil during the 2023 winter season, with the aim of developing and evaluating the efficiency of the performance of a combined and advanced machine used for planting on lines with equal distances and appropriate depths, with covering the seeds and appropriate disintegration of the soil using spring needles, fertilizing at the same time, and opening the furrows. Using separators after attaching them to the seeder. The experiment was carried out using two machine configurations: the seeder alone (B) and the seeder with the furrow opener (BZ), which is equivalent to basin irrigation system and furrows, and two tractor speeds (s1, s2) (4 and 6 km/h), with the aim of knowing its effect on (moisture content and field efficiency). The same two formulations and speeds above were also used with three barley seed rates (T1, T2, T3) kg/dunum in order to determine their effect on (plant height and grain yield). The (W2) composition gave a decrease in field efficiency, as it was recorded (86.338%). The (W2) composition gave a decrease in moisture content (15,203%), plant height (109.47) cm, and grain yield (3,523) tons/ha. The (W1) composition gave the highest average of field efficiency, reaching (88.805%). The composition (W1) resulted in a decrease in average plant height, reaching 113.36 cm, moisture content (22,648%), and grain yield (4,028) tons/ha. The third seed rate (T3) gave the highest average of grain yield, reaching (4,168) tons/ha, and plant height (113.58) cm. The second speed (S2) gave the highest average of field efficiency (88,643%), moisture content (19,173%), plant height (110,778) cm, and grain yield (3,774) tons/ha. The interaction treatment (w1t3) recorded the highest plant height. The interaction treatment (s1t3) recorded the highest grain yield, reaching 4,317 kg/ha